ISLAMIC STRATEGIC MANAGEMENT OF VILLAGE OWNED ENTERPRISES IN INCREASING VILLAGE ORIGINAL INCOME - Nasfi Nasfi; Sabri Sabri; Suhatman Suhatman; Rizda Octaviani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Background. Each Nagari or village has the potential to be developed in order to increase the income and welfare of its people , one of which is the management of Village Owned Enterprises or BUMNag through good managerial skills by the leader of the organization, moreover the leader is based on Islam, according to the philosophy of West Sumatra,